Antivascular Endothelial Growth Factor Monotherapy for Choroidal Neovascularization Associated With Retinochoroidal Coloboma: Case Series. Issue 5 (September 2016) - Bondalapati, Sailaja; Jalali, Subhadra; Chhablani, Jay
Abstract : Purpose: This study aimed to report the outcomes of antivascular endothelial growth factor (anti-VEGF) monotherapy for choroidal neovascularization (CNVM) associated with retinochoroidal coloboma (RCC). Design: A retrospective case series. Methods: This was a case series of 3 eyes with CNVM associated with RCC that presented to the LV Prasad Eye Institute, Hyderabad, India, between January 2006 and January 2014. Reported data included demographics, preoperative details (symptoms, duration of symptoms, and visual acuity), treatment methods, and postoperative details (visual acuity, follow-up, and recurrence). These data were compared with 9 other cases previously reported in the literature. Results: Three eyes of 3 patients (2 females and 1 male) were included, with a mean age of 18.3 years (range, 2–32 years). The preoperative best corrected visual acuity ranged from 20/540 to 20/100. All 3 eyes were treated with intravitreal bevacizumab injections. The mean number of injections was 2.0 (range, 1–3) and mean duration of follow-up was 12 months (range, 4–24 months) with no recurrence. The best corrected visual acuity at the last follow-up was improved, ranging from 20/310 to 20/60. Conclusions: In view of good treatment outcomes with no recurrence and a lesser number of injections, anti-VEGF monotherapy could be considered as treatment for coloboma-associated CNVM.